Analysis of the overlap section in a high-speed railway catenary by means of numerical simulations. (15th October 2020) - Gregori, S.; Gil, J.; Tur, M.; Tarancón, J.E.; Fuenmayor, F.J.
Highlights: A catenary Finite Element model is enhanced by considering double cantilevers and tensioning devices. The pantograph-catenary dynamic interaction in overlap sections is studied in a wide range of scenarios. The effect of the tensioning devices' efficiency is analysed. The geometry of an entire catenary section is optimised by means of Bayesian Optimisation techniques. Abstract: The transition between catenary tensioning sections is accomplished smoothly by overlapping a number of spans in each catenary section. This work presents an analysis of the overlap section in a high-speed railway catenary based on numerical simulations. The paper studies the influence on the system's dynamic behaviour of features such as double cantilevers and tensioning devices efficiency. Four and five-span overlaps are compared and the effect of train speed and overlap contact wire geometry are also analysed. Finally, an entire catenary section is optimised by Bayesian Optimisation techniques, leading to a catenary configuration with an interaction force with a standard deviation notably lower than that provided by the nominal catenary design.